2009
DOI: 10.1128/aem.02530-08
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characterization of Salmonellae in Commercial Ground Beef in the United States

Abstract: Commercially produced ground beef samples (n ‫؍‬ 4,136) were collected from seven regions of the United States over a 24-month period (July 2005 to June 2007) and analyzed for the presence of Salmonella enterica by using methods that concurrently provided total prevalence and enumerable levels. The overall prevalence of Salmonella strains was 4.2%. Enumeration showed that 94.2% were present at levels below 2 CFU/g. Regional monthly prevalences of Salmonella strains varied from 1.8% to 6.5% but were not statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(82 citation statements)
references
References 26 publications
1
77
2
2
Order By: Relevance
“…The variations in Salmonella and pathogenic E. coli prevalence amongst different countries could be attributed to a number of factors (including the farming systems and practices, slaughtering practices and post slaughter handling of meat as well as the general hygiene at different stages of the meat chain); which differ from one country to another. Higher prevalences are principally observed in developing countries, where poor hygienic conditions during slaughtering and meat handling are generally reported (Gashe & Mpuchane, 2000;Hassanein et al, 2011;Magwira, Gashe, & Collison, 2005;Stevens et al, 2006), whereas lower prevalence are mostly observed in developed countries where good hygienic practices are reported to be strictly followed and monitored along the meat chain (EFSA and ECDC, 2013;Vipham et al, 2012;Bosilevac et al, 2009). …”
Section: Salmonella and Pathogenic E Coli In Bovine Meatmentioning
confidence: 99%
See 1 more Smart Citation
“…The variations in Salmonella and pathogenic E. coli prevalence amongst different countries could be attributed to a number of factors (including the farming systems and practices, slaughtering practices and post slaughter handling of meat as well as the general hygiene at different stages of the meat chain); which differ from one country to another. Higher prevalences are principally observed in developing countries, where poor hygienic conditions during slaughtering and meat handling are generally reported (Gashe & Mpuchane, 2000;Hassanein et al, 2011;Magwira, Gashe, & Collison, 2005;Stevens et al, 2006), whereas lower prevalence are mostly observed in developed countries where good hygienic practices are reported to be strictly followed and monitored along the meat chain (EFSA and ECDC, 2013;Vipham et al, 2012;Bosilevac et al, 2009). …”
Section: Salmonella and Pathogenic E Coli In Bovine Meatmentioning
confidence: 99%
“…In some studies the number of analyzed samples amounted to thousands (Bosilevac et al, 2009;EFSA and ECDC, 2013b) , whereas in others only a very limited number of samples was analysed (Gashe & Mpuchane, 2000;Temellİ, Eyİgör, & Anar, 2012). Differences were also observed in sampling methodology, where the surface swabbed on bovine carcasses to detect pathogens or the weight of the meat samples analysed varied between different studies.…”
Section: Salmonella and Pathogenic E Coli In Bovine Meatmentioning
confidence: 99%
“…Cerro, Meleagridis, Typhimurium, Dublin and Kentucky [7]. These ten Salmonella serovars also have been associated with outbreaks of foodborne illness: Montevideo [8,9], Anatum [10], Muenster [11], Mbandaka [8], Agona [12], Cerro [13,14], Meleagridis [15], Typhimurium [16][17][18], Dublin [19,20] and Kentucky [21,22], to list a few instances.…”
Section: Journal Of Food Chemistry and Nanotechnology | Volume 3 Issumentioning
confidence: 99%
“…Recently, the Salmonella serovars Anatum, Montevideo and Kentucky were identified in cattle feces during a study to determine the prevalence of Salmonella enterica in South Texas beef cattle feedlots [29]. These Salmonella serovars are among the top 10 Salmonella serovars isolated from commercial ground meat [7], and can be important players in outbreaks of foodborne illness [8-10, 21, 22].…”
Section: Journal Of Food Chemistry and Nanotechnology | Volume 3 Issumentioning
confidence: 99%
“…bacteria are among the major pathogenic microorganisms transmitted by food in the world (CDC, 2011), and animal-derived products are the main carriers of this bacterium (BOSILEVAC et al, 2009;MURMANN et al, 2009). Salmonella Enteritidis and Salmonella Typhimurium are the main serovars isolated from human sources (CDC, 2011).…”
Section: Introductionmentioning
confidence: 99%